(untitled) (Transport systems and technologies, 2018)
In paper the technique of an estimation of economic efficiency of application of service of the main diesel locomotives is considered. Last researches on the given problem are analyzed. It is certain, that the given approach demands creation of essentially new methodical maintenance. Statistical data on real expenses for maintenance service and repair of diesel locomotives which have formed the basis for development of a special technique are collected. On the basis of the offered recurrent dependences in view of parameters of reliability of diesel locomotives in operation functions of relative expenses on labours input on maintenance service are certain. Thus likelihood variants, both in view of service and without it, were modeled. On the basis of it graphic dependences of relative labors expenses for maintenance service and criterion functions of their specific components depending on size of run of diesel locomotives are received. The offered technique calculation allows to define economic benefit for the accepted conditional park of diesel locomotives.